Isolation of T cell receptor specifically reactive with autologous tumour cells from tumour-infiltrating lymphocytes and construction of T cell receptor engineered T cells for esophageal squamous cell carcinoma. Issue 1 (28th August 2019) - Tan, Qin; Zhang, Chaoting; Yang, Wenjun; Liu, Ying; Heyilimu, Palashati; Feng, Dongdong; Xing, Liying; Ke, Yang; Lu, Zheming
Abstract : Background: T cell receptor-engineered T cells (TCR-Ts) therapy is a promising cancer treatment strategy. Nowadays, most studies focused on identification of high-avidity T cell receptors (TCRs) directed against neoantigens derived from somatic mutations. However, few neoantigens per patient could induce immune response in epithelial cancer and additionally many tumor-specific antigens could be derived from noncoding region. Autologous tumor cells (ATCs) could be unbiased stimulators in activating and enriching tumor-reactive T cells. However, it's unknown if T cells engineered to express TCRs isolated from tumor-reactive T cells enriched by ATCs have strong antitumor response. Methods: In this study, multiple TIL fragments obtained from a patient with esophageal squamous cell carcinoma (ESCC) were screened for specific recognition of ATCs. Tumor-reactive TILs were enriched by in vitro repeated stimulation of ATCs and isolated based on CD137 upregulation. Subsequently, tumor-reactive TCR was obtained by single-cell RT-PCR analysis and was introduced into peripheral blood lymphocytes to generate TCR-Ts. Results: We found that phenotype and effect function of TIL fragments derived from different tumor sites were spatially heterogeneous. Of four TIL fragments, only TIL-F1 could specifically identify ATCs. Subsequently, we isolated CD8 + CD137 + T cells from pre- and post-stimulated TIL-F1 co-cultured with ATCs, and identified their most dominant TCR. This TCR was introduced into PBLs to generate TCR-Ts, which specifically identified and killed ATCs in vivo and in vitro. Conclusion: This strategy provides the means to generate tumor-reactive TCR-Ts for ESCC, which is especially important for patients without prior knowledge of specific epitopes and might be applied for other cancers.